Seagrass communities on the North Coast of Aceh - Khairunnisa Khairunnisa; Zuhilma Dewi Arie; Ramadhani Pitri; Farahisah Harum (BIO Web of Conferences)
Seagrass density and biomass are key indicators of the health and productivity of seagrass ecosystems. This study aims to address the seagrass communities on the North Coast of Aceh. Seagrass data collection was conducted using the Seagrass Net parallel transect plot method. The data analyzed include density, biomass, and carbon estimates. Three species of seagrass have been identified in the northern waters of Aceh, include Halodule pinifolia Halophila ovalis, and Halophila minor. Seagrass density ranged between 301 - 440 ind/m2. the dry biomass measurements across various seagrass species and research stations indicate that the belowground biomassa generally exceeds the above ground biomass. The carbon stock at the research site ranged from 58.85 to 69.82 g C/m². By focusing on species diversity, density, biomass, and estimation of carbon storage capacity, this research will provide valuable insights into the ecological and carbon storage functions of seagrass ecosystems in this region, contributing to their conservation and sustainable management.